The effect of microbial activity on soil water diffusivity. (30th January 2018) - Choudhury, B. U.; Ferraris, S.; Ashton, R. W.; Powlson, D. S.; Whalley, W. R.
Abstract : In this study, we explored the effects of microbial activity on the evaporation of water from cores of a sandy soil under laboratory conditions. We applied treatments to stimulate microbial activity by adding different amounts of synthetic analogue root exudates. For comparison, we used soil samples without synthetic root exudates as control and samples treated with mercuric chloride to suppress microbial activity. Our results suggest that increasing microbial activity reduces the rate of evaporation from soil. Estimated diffusivities in soil with the largest amounts of added root exudates were one third of those estimated in samples where microbial activity was suppressed by adding mercuric chloride. We discuss the effect of our results with respect to water uptake by roots. Highlights: We explored effects of microbial activity on the evaporation of water from cores of a sandy soil. We found the effect of microbial activity on water release characteristic was small. Increasing microbial activity reduced evaporation from soil, while microbial suppression increased it. Effect of microbial activity on root water uptake was estimated to be equivalent to a change in soil structure.